Metabolism of dihydrouracil in Rhodosporidium toruloides. - Davis, C H (1984)
Previous studies, including those done with a similar species, have indicated that dihydrouracil is formed by the breakdown of uracil and is degraded into N-carbamyl-beta-alanine. (Fink et al., J. Biol. Chem. 201:349-355, 1953; S. R. Vilks and M. Y. Vitols, Mikrobiologiya 42:567-583, 1973; O. A. Milstein and M. L. Bekker, J. Bacteriol. 127:1-6, 1976). In the present work the conversion of dihydrouracil to uracil is studied in Rhodosporidium toruloides, and the growth characteristics of mutants that have lost the ability to use dihydrouracil as a source of nitrogen are examined. It is concluded that dihydrouracil must be converted to uracil before catabolism of the pyrimidine ring can take place.